2002
DOI: 10.1139/x01-224
|View full text |Cite
|
Sign up to set email alerts
|

An improved trap for large wood-boring insects, with special reference to Monochamus scutellatus (Coleoptera: Cerambycidae)

Abstract: Commercially available multiple funnel traps have three potential limitations for trapping large wood-boring insects: (i) escape by captured insects from the dry collecting cup, (ii) low catches of insects that fall outside the trap, and (iii) poor visual orientation to the narrow funnel column. To test the importance of these limitations, we compared conventional multiple funnel traps to multiple funnel traps with water-filled collecting cups or large bottom funnels and to crossvane traps with a prominent sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(100 citation statements)
references
References 12 publications
8
87
5
Order By: Relevance
“…The importance of visual cues in host selection behavior has been reported in many phytophagous insects [2,4,10,19,24], and studies have demonstrated that visual cues are used in the host-finding behavior of Cerambycid species [8,17,18]. Further studies on how visual cues are utilized in combination with attraction to host volatiles should clarify the host selection precess of M. alternatus.…”
Section: Discussionmentioning
confidence: 90%
“…The importance of visual cues in host selection behavior has been reported in many phytophagous insects [2,4,10,19,24], and studies have demonstrated that visual cues are used in the host-finding behavior of Cerambycid species [8,17,18]. Further studies on how visual cues are utilized in combination with attraction to host volatiles should clarify the host selection precess of M. alternatus.…”
Section: Discussionmentioning
confidence: 90%
“…The insecticide prevented beetles from escaping from the funnel traps and allowed us better to compare the capture levels of the two trap types (Allison et al 2001(Allison et al , 2003Morewood et al 2002;Pajares et al 2004). Traps were examined weekly.…”
Section: Methodsmentioning
confidence: 99%
“…Allison et al (2003) suggest that adding the bark beetle pheromone(s) ipsenol and/or ipsdienol to α-pinene and ethanol baits may be cost-effective. Recent advances in trap designs for coniferophagous woodborers (de Groot & Nott 2001;Morewood et al 2002a) should also improve the efficacy of mass trapping programs.…”
Section: Referencementioning
confidence: 99%
“…Similarly, M. scutellatus responded equally to traps of various designs baited with host volatiles early in the flight season, when maturation feeding occurs. In the latter half of the flight season, when oviposition occurs, they were most responsive to baited traps presenting a prominent, dark silhouette, suggestive of their larval hosts (Morewood et al 2002a). The chemistry governing interactions among members of the larval insect community below the bark has yet to be investigated.…”
Section: Future Research Directionsmentioning
confidence: 99%